Feature-Driven 3D Building Modeling using Planar Halfspaces - M. Kada; A. Wichmann (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
With the exception of pure data-driven methods, reconstruction approaches for 3D building models from aerial point clouds often incorporate some level of model information to construct regularized and well-formed roof structures. In the proposed feature-driven approach, low-level roof features like ridge lines, gable and (half-) hip ends, intersecting ridge lines, dormers etc. are detected in a hierarchical rule-based feature recognition process based on a sub-surface segmentation of the point cloud. With each feature type, a number of planar half-spaces are associated that define a certain part of the resulting 3D building model as a mathematical inequality equation. The Boolean intersection of half-spaces define convex building components that can be united to generate more complex building shapes, where the features enforce that the half-spaces are nicely aligned.